THE REPRESENTATIONS OF YOUNG WOMENIN PRINT ADVERTISEMENTS OF COSMOGIRL MAGAZINE - Dhyah Mutmainnah, - (2008)
The present study investigated the representations of young women in selected print advertisements in Cosmogirl Magazine. Five print advertisements in Cosmogirl Magazines were selected as the primary data to be analyzed. The data were categorized based on the best satisfaction toiletries products which were targeted for women to determine the young women characteristics. As a descriptive-qualitative research, this study uses semiotic tools to reveal representations of young women in the advertisements. The images of the advertisement were analyzed by using Kress and van Leeuwen's visual text analysis. Meanwhile, the verbal texts of those advertisements were analyzed by using Hallidayan modality. The findings clearly show that the selected print advertisements reflect representations of young women of Cosmogirl Magazine. The young women are represented as easy-going, casual, who do their daily activities in a simple way, especially in taking care of their face, body, and hair, to keep them beauty and health. The result of this research will add to the literature on women portrayals in advertisements by examining closely the relationship between women and sexuality in advertisements that exploit women to sell products.